Effects of crab burrows on pore water flows in salt marshes - Xin, Pei; Jin, Guangqiu; Li, Ling; Barry, D.A. (Advances in water resources, 2009)
Macro-pores such as crab burrows are found commonly distributed in salt marsh sediments. Their disturbance on the soil structure is likely to influence both pore water flows and solute transport in salt marshes; however, the effects of crab burrows are not well understood. Here, a three-dimensional model simulated tidally driven pore water flows subject to the influence of crab burrows in a marsh system. The model, based on Richards’ equation, considered variably saturated flow in the marsh with a two-layer soil configuration, as observed at the Chongming Dongtan wetland (Shanghai, China). The simulation results showed that crab burrows distributed in the upper low-permeability soil layer, acting as preferential flow paths, affected pore water flows in the marsh particularly when the contrast of hydraulic conductivity between the lower high-permeability soil layer and the overlying low-permeability soils was high. The burrows were found to increase the volume of tidally driven water exchange between the marsh soil and the tidal creek. The simulations also showed improvement of soil aeration conditions in the presence of crab burrows. These effects may lead to increased productivity of the marsh ecosystem and enhancement of its material exchange with coastal waters.